2006
DOI: 10.1164/rccm.200410-1369oc
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Death of Patients with Cystic Fibrosis Awaiting Lung Transplantation

Abstract: We identified risk factors for waiting list mortality that could impact on transplant listing and allocation guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
114
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 36 publications
5
114
1
6
Order By: Relevance
“…The fact that CF is associated with a strong impact on Ppa and right ventricle function had long been demonstrated [6][7][8], bearing a strongly negative prognostic value [10,12]. Their exact frequency is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that CF is associated with a strong impact on Ppa and right ventricle function had long been demonstrated [6][7][8], bearing a strongly negative prognostic value [10,12]. Their exact frequency is not known.…”
Section: Discussionmentioning
confidence: 99%
“…First, CF is a widely distributed chronic obstructive lung disease in which PH and right-sided cardiac failure have long been described [6][7][8][9]. Although PH seems to be relatively rare in this context, it is recognised as a very significant clinical issue with a heavy impact on the prognosis [10][11][12].…”
mentioning
confidence: 99%
“…It is possible to act on intracellular events and encourage, correct or potentiate the synthesis of mutated CFTR-a (Ivacafor, Lumocaftor, Ataluran), (15,16,17). In the fi nal stage lung disease is available and lung transplantation, individuals with CF must have both lungs replaced because the remaining lung might contain bacteria that could infect the transplanted lung (18). Although the lifespan moved from childhood to adult age, patients are still faced with an abundance of therapeutic needs, and their doctors with a new pathology.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that ''patients with CF should be referred for transplantation at a time when based on their rate of decline in lung function, the expected time for their percent predicted FEV 1 to reach 20% equals the average local waiting time for donor lungs, or when the baseline percent predicted FEV 1 reaches 30%, whichever comes first.'' Finally, a retrospective cohort study of 343 patients listed for lung transplantation at four academic medical centers was used to generate a multivariate model of waiting list mortality (18 3; 95% CI, 1.3-4.1) were at higher risk. The authors concluded that ''on the basis of these data, the presence of hypercapnia in the setting of better lung function and the requirement for nutritional interventions are additional factors that should be considered in developing future models to be used in allocating organs to the CF population'' (18).…”
Section: Pediatric Lung Transplantation For Cystic Fibrosis: Overviewmentioning
confidence: 99%
“…Finally, a retrospective cohort study of 343 patients listed for lung transplantation at four academic medical centers was used to generate a multivariate model of waiting list mortality (18 3; 95% CI, 1.3-4.1) were at higher risk. The authors concluded that ''on the basis of these data, the presence of hypercapnia in the setting of better lung function and the requirement for nutritional interventions are additional factors that should be considered in developing future models to be used in allocating organs to the CF population'' (18).…”
Section: Pediatric Lung Transplantation For Cystic Fibrosis: Overviewmentioning
confidence: 99%